Integrins control epithelial stem cell proliferation in the Drosophila ovary by modulating the Notch pathway - Rincón-Ortega, Lourdes; Valencia-Expósito, Andrea; Kabanova, Anna; González-Reyes, Acaimo; Martin-Bermudo, Maria D. (Frontiers in Cell and Developmental Biology, 2023)
Cell proliferation and differentiation show a remarkable inverse relationship. The temporal coupling between cell cycle withdrawal and differentiation of stem cells (SCs) is crucial for epithelial tissue growth, homeostasis and regeneration. Proliferation vs. differentiation SC decisions are often controlled by the surrounding microenvironment, of which the basement membrane (BM; a specialized form of extracellular matrix surrounding cells and tissues), is one of its main constituents. Years of research have shown that integrin-mediated SC-BM interactions regulate many aspects of SC biology, including the proliferation-to-differentiation switch. However, these studies have also demonstrated that the SC responses to interactions with the BM are extremely diverse and depend on the cell type and state and on the repertoire of BM components and integrins involved. Here, we show that eliminating integrins from the follicle stem cells (FSCs) of the Drosophila ovary and their undifferentiated progeny increases their proliferation capacity. This results in an excess of various differentiated follicle cell types, demonstrating that cell fate determination can occur in the absence of integrins. Because these phenotypes are similar to those found in ovaries with decreased laminin levels, our results point to a role for the integrin-mediated cell-BM interactions in the control of epithelial cell division and subsequent differentiation. Finally, we show that integrins regulate proliferation by restraining the activity of the Notch/Delta pathway during early oogenesis. Our work increases our knowledge of the effects of cell-BM interactions in different SC types and should help improve our understanding of the biology of SCs and exploit their therapeutic potential.